A reader's companion to Mikhail Bulgakov's The master and Margarita - Curtis, J. A. E. (Companions to Russian literature, 2019)
Bulgakov's Life: Formative Years and First Successes-1891-1928 -- Bulgakov's Life: Battling the Censor, and Writing The Master and Margarita-1929-1940 -- The Master and Margarita: Drafts and Final Version -- Publication History of The Master and Margarita in Russian -- A Tale of Two Cities: The Structure of The Master and Margarita -- Woland: Good and Evil in The Master and Margarita -- Pilate and Ieshua: Biblical Themes in The Master and Margarita -- Political Satire in The Master and Margarita -- Literature and the Writer in The Master and Margarita -- "So who are you, then?": Narrative voices in The Master and Margarita, followed by a Stylistic Analysis of Extracts from the Text -- English Translations of The Master and Margarita -- Afterword: A Personal Reflection